2022
DOI: 10.3389/fbioe.2022.1024871
|View full text |Cite
|
Sign up to set email alerts
|

Emerging applications of nanotechnology in context to immunology: A comprehensive review

Abstract: Numerous benefits of nanotechnology are available in many scientific domains. In this sense, nanoparticles serve as the fundamental foundation of nanotechnology. Recent developments in nanotechnology have demonstrated that nanoparticles have enormous promise for use in almost every field of life sciences. Nanoscience and nanotechnology use the distinctive characteristics of tiny nanoparticles (NPs) for various purposes in electronics, fabrics, cosmetics, biopharmaceutical industries, and medicines. The exclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 172 publications
(197 reference statements)
0
10
0
Order By: Relevance
“…Fecal pellets and 100 μl blood obtained by the orbital sinus route were collected on Days 27, 41, and 55. Anti-IpaD and -IpaB IgG and IgA titers were determined as previously described with minor modifications ( 23 ). Briefly, microtiter plate wells were coated with 100 ng IpaB or IpaD in 100 µl PBS and incubated at 37°C for 3 h. Wells were blocked with 10% nonfat dry milk in PBS overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fecal pellets and 100 μl blood obtained by the orbital sinus route were collected on Days 27, 41, and 55. Anti-IpaD and -IpaB IgG and IgA titers were determined as previously described with minor modifications ( 23 ). Briefly, microtiter plate wells were coated with 100 ng IpaB or IpaD in 100 µl PBS and incubated at 37°C for 3 h. Wells were blocked with 10% nonfat dry milk in PBS overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown a better response is elicited in humans when the antigen is presented as a multimer in the context of a nanoparticle ( 21 , 22 ). There are nanoparticle formulations currently being tested for use in intramuscular and intranasal vaccines ( 23 25 ). The most well-known multimerization method is the use of aluminum salts such as Alhydrogel; however, aluminum salts tend to skew the resulting immunity to a Th2 response, which is more aligned with the humoral response and not the balanced responses often required for clearing mucosal pathogens ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, its lethal oxidation problem and lack of biological compatibility sometimes outweigh its benefits [ 500 ]. A substance created by biogeochemical processes spontaneously, free from human intervention, is referred to as a natural nanomaterial [ 501 ]. The detection of H2O2 in pharmaceutical, food, clinical, industrial, and environmental assessments could be facilitated by the bonding ability and biocompatibility of Se nanomaterial crystals with the HRP (horseradish peroxidase) biosensor [ 502 ].…”
Section: Challenges and Considerationsmentioning
confidence: 99%
“…This Review does not address the immunological aspects of nanotechnology. To improve and expedite treatment, we do, however, offer updated data that will investigate new theragnostic immunological applications of nanotechnology [ 507 ]. Even though cytotoxic chemicals are thought to have immunosuppressive effects, accumulating data indicates that certain cytotoxic substances may successfully activate the immune response against tumors by causing a particular kind of apoptosis known as immunogenic cell death (ICD).…”
Section: Challenges and Considerationsmentioning
confidence: 99%
See 1 more Smart Citation